Toward a substantive theory of control of learning within grassroots initiatives - Joyce S. McKnight (Adult Education Research Conference, 1994)
This study uses the grounded theory building methods of Glaser and Strauss (1967) to produce a substantive theory of the control of learning within the context of grassroots initiatives.